Komunikasi Penyelesaian Konflik PT Nusajaya Persadatama Mandiri dan Masyarakat Lingkar Tambang Desa Matarape, Kabupaten Morowali - Hasmita (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2024)
This study looks at the Conflict Resolution Communication model using descriptive qualitative research methods, through a conflict management model approach. The research subjects of PT Nusajaya Persadatama Mandiri (NPM) with the object of the research are several who work in the company (Humas Team, KTT), village officials and also the community. The results of this study used the company's steps, namely: 1) did not meet the people of Matarape Village directly, 2) accommodating community demands through the village government, 3) considering the demands and also the rules that must be met by the company, 4) transfer of Fee (cash) to Community Empowerment Program (PPM), 5) Community Empowerment Program is a solution in the conflict resolution process. The program which initially became a problem in the community due to a lack of public understanding regarding the Community Empowerment Program (PPM) made the community prefer cash fees, but some programs that have been realized can be directly benefited by the village community.